Workplace training and generic and technical skill development in the Australian construction industry. Issue 4 (9th May 2016) - Detsimas, Nicole; Coffey, Vaughan; Sadiqi, Zabihullah; Li, Mei
Abstract : Purpose: – The purpose of this paper is to investigate the current skills gap in both generic and skill areas within the construction industry in Queensland, Australia. Design/methodology/approach: – An internet-based survey was administered to collect the opinions of construction employees about the workplace-training environment and their perceptions towards training. The survey intended to address the following research questions, specifically in relation to the construction industry. Findings: – The survey results reveal that whilst overall participation in workplace training is high, the current workplace training environments do not foster balanced skill development. The study reveals that in the current absence of a formal and well-balanced training mechanism, construction workers generally resort to their own informal self-development initiatives to develop the needed role-specific theoretical knowledge. Research limitations/implications: – The findings of the research are based on the data primarily collected in the construction industry in Queensland, Australia. The data are limited to a single Tier 2 construction company. Practical implications: – The findings of this study can be utilised to suggest improvements in the current (or develop new) workplace training initiatives. Social implications: – The research suggests that workplace training has positive relationship with career growth. The results suggest that in the construction industry, employees are generally well aware of the importance of workplace training in their career development and they largely appreciate training as being a critical factor for developing their capacity to perform their roles successfully, and to maintain their employability. Originality/value: – This paper is unique as it investigates the current skills gap in both generic and skill areas within the construction industry in Queensland, Australia. So far no work has been undertaken to identify and discusses the main method of workplace learning within the Tier 2 industry in the context of Queensland Australia.